SISTEM MONITORING SUHU UNTUK MENJAGA KETAHANAN PRODUK MAKANAN TERHADAP RUANG PENYIMPANAN DENGAN MOTODE FUZZY LOGIC - Makmun Effendi; Feri Wartono; Elkin Rivalni (Jurnal Pelita Teknologi, 2019)
Temperature in storage room is one of the factors that affects the durability of food. The food when be placed at an inappropriate temperature within a certain period, will cause slimy, smelled of acid, crushed, clot, bacteria can grow faster so that the product's life time will decrease. Therefore, in every storage room must be very concerned in every change of temperature. This research aims to create a set of tools that can monitor the temperature of storage room automatically. The tool will read the high and low temperature in real time using the DS18B20 sensor as a temperature data taker. The data will be processed to produce an output analysis of product durability in the storage room temperature using fuzzy logic method. In this research, the system can display temperature data and the results of the temperature monitoring process so that the system can be implemented and run as a requirement. Keywords:fuzzy logic; monitoring system; temperature